Blockchain En El Sector De Los Videojuegos: Modelo De Negocio Canvas (2022)
The business model came from the search for an idea that allows companies that are dedicated to the area of video games to make the most of all their capabilities and statistics. Considering that the world of video games is one of the sectors with the highest income today, and our handling of blockchain technology as an emerging technology, it is decided to concatenate both technologies and implement a business model. It is appropriate that both authors of this document are fans of video games and have knowledge of economics and programming. A business model is agreed taking into account the experiences of each one, the complaints that exist in the sector despite the fact that the objectives of these companies are to meet the expectations of users in terms of entertainment. The objectives that were set for the execution, in addition to some functions, are: - Facilitate the search of statistics by player name - Carry out the same process on different platforms - Offer personalized data to developers Through data storage techniques such as Big Data, the aim is to offer the user a series of data and statistics on players to feel attracted to the project, due to the management of the authors of this project in programming, an application with interaction in time was developed real that allows you to access a database, log in to the application and obtain data in real time.